Perancangan Mesin Pencuci Karpet Menggunakan Tabung Cairan Deterjen - Anissa Vivia Fidela; Dandi Ilham; Haris Haris; Ruzita Sumiati; Yuliarman Yuliarman; Yuli Yetri (Jurnal Teknik Mesin, 2022)
Carpet washer is a machine that is used to help complete work in the laundry industry. By using this carpet cleaning machine, cleaning carpets is fast and easy. The purpose of designing this carpet washing machine is a form of innovation and creativity based on technological developments. This machine is made with an additional tube of liquid detergent to make work easier and increase efficiency. The initial method of designing this carpet washing machine is to collect data. Next is the calculation and design. The results of the design of this carpet washing machine obtained a motor power of 1.5 HP and a rotation of 1400 rpm, with a height of 1020 mm, a length of 745 mm and a width of 345 mm using a type-A belt transmission, pulleys with a diameter of 2” and 6”, a shaft diameter of 19 mm, the type of bearing used is UCF F212 type, has a cleaning brush and uses a liquid detergent tube. The design of this carpet washing machine has been made based on the correct design and calculation and can be continued for production.